Fault detectability in DWDM : - Kartalopoulos, Stamatios V. (IEEE Press, 2001)
Enhance your understanding of the failure mechanisms of optical components, and draft fault detection guidelines to design a robust Dense Wavelength Digital Multiplexing (DWDM) system and network that exhibits and maintains optical signal quality and system reliability.